Optimization of a Method to Isolate and Culture Adult Porcine, Rats and Mice Müller Glia in Order to Study Retinal Diseases - Pereiro, Xandra; Ruzafa, Noelia; Acera, Arantxa; Urcola, Aritz; Vecino, Elena (Frontiers in Cellular Neuroscience, 2020)
Müller cells are the predominant glial elements in the retina, extending vertically across this structure, and they fulfill a wealth support roles that are critical for neurons. Alterations to the behavior and phenotype of Müller glia are often seen in animal models of retinal degeneration and in retinal tissue from patients with a variety of retinal disorders. Thus, elucidating the mechanisms underlying the development of retinal diseases would help better understand the cellular processes involved in such pathological changes. Studies into Müller cell activity in vitro have been hindered by the difficulty in obtaining pure cell populations and the tendency of these cells to rapidly differentiate in culture. Most protocols currently used to isolate Müller glia use neonatal or embryonic tissue but here, we report an optimized protocol that facilitates the reliable and straightforward isolation and culture of Müller cells from adult pigs, rats and mice. The protocol described here provides an efficient method for the rapid isolation of adult mammalian Müller cells, which represents a reliable platform to study therapeutic targets and to test the effects of drugs that might combat retinal diseases.